Valorization of white wine grape pomace through application of subcritical water: analysis of extraction, hydrolysis, and biological activity of the extracts obtained - Pedras, Bruno (2019)
White wine grape pomace (WWGP) was treated with subcritical water in a semi-continuous reactor, at 170, 190 and 210 °C. Assays at 210 °C led to highest recovery of carbohydrates (85% of total amount of carbohydrates of WWGP) and phenolic compounds (2.6 g/100 gWWGP). Moreover, 48% of initial lignin was solubilized. The amount of carbohydrates recovered increased sharply in the initial stages of the process, due to the extraction of soluble carbohydrates, and then less pronouncedly, as hydrolysis of WWGP took place. The difference in the progress curves for the yields of carbohydrates and of phenolics allowed the separate recovery of carbohydrate-rich, and phenolics-enriched, GP extracts. The latter exhibited 10 times higher antioxidant activity (AA) than a GP extract obtained by hydro-alcoholic extraction, and 8 times lower AA than pure ascorbic acid. WWGP extracts were also found to have 4 times higher antimicrobial activity against Gram-positive than Gram-negative bacteria.